Scrofula, a frequent form of extrapulmonary tuberculosis. Case presentation - Maria Elena Palma Lopez (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: The forms of presentation of the tuberculosis (Tb) include: the pulmonary, miliaria and extrapulmonary tuberculosis. Outside of the lung, the where places with major frequency localizes tuberculosis are, by order of frequency: lymphatic ganglions, pleura, genitourinary system, bones and joints, meninges, peritoneum and pericardium. Objective: To present an interesting case in the clinic of extrapulmonary Tb and lung Tb. Case presentation: Masculine 65-years patient of age, chronic alcoholic and smoker. That began to present an increase of volume in the lateral right region of the neck that went growing progressively; besides humid cough with whitish expectoration, dysphagia to the solid foods, asthenia, anorexia and loss of weight. The physical examination made evident multiple cervical suppurative adenopathias, the major of 6cm and crepitating rasps at the superior third of the right hemi-thorax. The Mantoux proof was positive and the thorax X-ray suggested a pulmonary TB. The patient was discharged with a treatment against tuberculosis and ambulatory antibiotic, which were abandoned by the patient. He was entered in second occasion in the service of geriatrics for ulceration of the major injury of the neck and dies at the third day for a generalized sepsis. Conclusions: The tuberculosis of the lymphatic ganglions is the more common presentation of the extrapulmonary tuberculosis. Illness attacks principally to the persons with low defenses and in the presented case the patient had factors that could have depressed his immune system as the age, the chronic alcoholism and the smoking  Keywords: Pulmonary tuberculosis, extrapulmonary tuberculosis, mantoux, scrofula.